The Historical Construction of the Mexican Transnational Community in Los Ángeles (1920-1940) - Pintor Sandoval, Renato; Gil Pérez, Anderson Paul (Sociedad y Economía, 2025)
The objective of this paper is to analyze the origin of the process of the Mexican transnational community in Los Angeles from the 1920s to the 1940s. Starting from the perspective of public spaces for “sociability” and everyday life, these helped to generate transnational degrees, helping the conformation of Mexican identity with the support of social support networks among migrants. The research develops the central elements of transnationalism: the references of inhabited public space, religious organizations, mutuals, media and practices, as well as the category of sociabilities of the historical discipline. The methodological design is qualitative in nature and articulates the historical events of the transnational community in the creation of the different “transnational spheres” of migrants and the development of practices in the Californian southeast.